Pandangan Religius Mengenai Autisme - Dwi Sari Usop; Muhammad Fatchurahman (Anterior Jurnal, 2016)
The existence of autism is a sign of greatness of Allah SWT. that must be considered positive. The presence of children with autism as a lesson for all mankind in treating others. As other children, persons with autism are also required to study religion, run, and practice the rules of religion.